How Has Nafta Affected the Mexican Economy? : Review and Evidence - Kose, Ayhan (IMF Working Papers; Working Paper ;, 2004)
This paper provides a comprehensive assessment of the impact of NAFTA on growth and business cycles in Mexico. The effect of the agreement in spurring a dramatic increase in trade and financial flows between Mexico and its NAFTA partners, and its impact on Mexican economic growth and business cycle dynamics, are documented with reference both to stylized facts and recent empirical research. The paper concludes by drawing lessons from Mexico's NAFTA experience for policymakers in developing countries. The foremost of these is that in an increasingly globalized trading system, bilateral and regional free trade arrangements should be used to accelerate, rather than postpone, needed structural reform.